Increasing productivity and profitability: evaluating diverse cropping systems. A field study in Chapainawabganj District in Bangladesh - Saiful Islam; Cheesman, Stephanie; Maruf Hossen Shanto; Md. Arifur Rahaman; Hossain, M. Khaled; Hossain, Shakhawat; Gathala, Mahesh Kumar; Krupnik, Timothy J. (TAFSSA, 2024)
The Barind Tract in Chapainawabganj, Bangladesh, covers 128,342 hectares (DAE, 2023) and faces severe agroecological challenges, including high temperatures, low soil moisture retention, and erratic rainfall. The region’s poorly drained, low-organic soils are prone to drought, limiting crop productivity (Ali et al., 2018). To address these issues, a participatory research trial (2022–2023) tested diversified and climate-resilient cropping systems against traditional practices. This brief summarizes key findings on productivity and economic efficiency, offering sustainable solutions for improving agricultural outcomes in this climate-sensitive region.